2012
DOI: 10.4238/2012.june.25.1
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of peritoneal metastasis-related genes of gastric adenocarcinoma using a cDNA microarray

Abstract: ABSTRACT. With the aim of identifying peritoneal metastasis-related genes in gastric cancer, we performed a broad analysis of differential gene expression between the parental cell line GC9811 and its highly metastatic peritoneal counterpart, cell line GC9811-P. Two fluorescent cDNA probes, labeled with Cy3 and Cy5 dyes, were prepared from GC9811 and GC9811-P mRNA samples by the reverse transcription method. The two color probes were then mixed and hybridized to a cDNA chip constructed with double-dots from 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Wu et al uncovered translationally upregulated genes in the context of epithelial to mesenchymal transition (EMT) using polysome profiling and found that six-transmembrane epithelial antigen of the prostate 1 ( STEAP1 ) is induced translationally and its expression promotes proliferation, migration, invasiveness, and tumorigenicity of gastric cancer [ 66 ]. Another similar cell line study revealed that recombinant human S100 calcium-binding protein A4 ( S100A4 ) and cadherin-associated protein β1 ( CTNNB1 ) were upregulated while phosphatase and tensin homolog deleted on chromosome tEN ( PTEN ) was downregulated in peritoneally disseminating cells [ 67 ]. Chen et al investigated molecular profiles and metastasis markers in Chinese patients with gastric carcinoma and unraveled mutation spectra and genomic regions associated with peritoneal metastasis.…”
Section: Tumor Genetic Changes Associated With Peritoneal Metastasismentioning
confidence: 99%
“…Wu et al uncovered translationally upregulated genes in the context of epithelial to mesenchymal transition (EMT) using polysome profiling and found that six-transmembrane epithelial antigen of the prostate 1 ( STEAP1 ) is induced translationally and its expression promotes proliferation, migration, invasiveness, and tumorigenicity of gastric cancer [ 66 ]. Another similar cell line study revealed that recombinant human S100 calcium-binding protein A4 ( S100A4 ) and cadherin-associated protein β1 ( CTNNB1 ) were upregulated while phosphatase and tensin homolog deleted on chromosome tEN ( PTEN ) was downregulated in peritoneally disseminating cells [ 67 ]. Chen et al investigated molecular profiles and metastasis markers in Chinese patients with gastric carcinoma and unraveled mutation spectra and genomic regions associated with peritoneal metastasis.…”
Section: Tumor Genetic Changes Associated With Peritoneal Metastasismentioning
confidence: 99%
“…Another comparative analysis between the parental cell line GC9811 and its highly metastatic peritoneal counterpart, cell line GC9811-P revealed and confirmed that recombinant human S100 calcium binding protein A4 (S100A4) and cadherin-associated protein beta 1 (CTNNB1) were upregulated and phosphatase and tensin homolog deleted on chromosome ten was downregulated in GC9811-P cells. Identification of these differentially expressed genes could disclose the molecular mechanisms involved and provide new targets for therapeutic intervention to avoid peritoneal dissemination of gastric adenocarcinoma[20]. A recent study revealed that intraoperative hemorrhages were strongly correlated with peritoneal recurrence, probably due to an increased ability of cancer cells and mesothelial cells to adhere to each other in the presence of factors in plasma[16].…”
Section: Molecular Mechanisms Of Peritoneal Metastasismentioning
confidence: 99%
“…A large body of evidence supports the calcium‐binding protein S100A4 role in control of invasion and metastasis in many invasive tumours. For example, cDNA microarray analysis of peritoneal metastasis in gastric adenocarcinoma indicates that the S100A4 and CTNNB1 genes encoding a subunit of E‐cadherin–β‐catenin were up‐regulated in the examined cell lines . S100A4 was also found to mediate the attraction and/or activation of T cells associated with promotion of metastatic spread .…”
Section: Cancer Cell–pleural and Peritoneal Cells Interaction In Cancmentioning
confidence: 99%